1998
DOI: 10.1038/sj.bjp.0701908
|View full text |Cite
|
Sign up to set email alerts
|

ATP and vasoactive intestinal polypeptide relaxant responses in hamster isolated proximal urethra

Abstract: 1 Nitric oxide (NO) is known from previous studies to be the principle transmitter in NANC inhibitory nerves supplying the hamster urethra. However, the identity of the cotransmitter(s) responsible for the responses remaining following block with L-N G -nitroarginine methyl ester (L-NAME) is not known. 6 In summary, these results are consistent with the view that ATP is an inhibitory transmitter released from inhibitory nerves supplying the NANC relaxation of hamster proximal urethra. The relaxant eect of ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The findings suggested that P2Y-purinoceptors exist in the male rabbit urethra, and that ATP and related purine compounds may play a role in NANC neurotransmission. This conclusion was further supported by Pinna et al (1998), who studied the effect of EFS on circular strips of hamster proximal urethra precontracted with arginine vasopressin. EFS caused frequency-dependent relaxations, which were attenuated by suramin and reactive blue.…”
Section: B Urethrasupporting
confidence: 59%
“…The findings suggested that P2Y-purinoceptors exist in the male rabbit urethra, and that ATP and related purine compounds may play a role in NANC neurotransmission. This conclusion was further supported by Pinna et al (1998), who studied the effect of EFS on circular strips of hamster proximal urethra precontracted with arginine vasopressin. EFS caused frequency-dependent relaxations, which were attenuated by suramin and reactive blue.…”
Section: B Urethrasupporting
confidence: 59%
“…In the pre-contracted proximal urethra of the hamster, NANC nerve stimulation and exogenous ATP were also shown to produce relaxations, which were attenuated by suramin and Reactive Blue 2, and to a lesser extent by 8-PT, but not by PPADS. ATP-induced relaxations were also reduced by indomethacin and were urothelium-and NOindependent, since they were not affected by removal of the urothelium or by the NOS inhibitor N ω -nitro-L -arginine methyl ester [561]. Thus, P2Y as well as P1 receptors appear to mediate the relaxing effect of ATP released from a NANC nerve pathway which has a subordinate role to the major nitrergic pathway.…”
Section: Urethramentioning
confidence: 81%
“…1b). Later studies have offered unequivocal support for this hypothesis (see [106]), not only in guinea-pig bladder [83,112,254,287,314,325,356,482,556,721], but also the bladders of many other species, including: mouse [4,301,682,714]; pig [253]; hamster [561]; marmoset and ferret [500]; dog [653] The prejunctional inhibition of both cholinergic and purinergic components of the nerve-mediated responses of the rat bladder by adenosine was taken as evidence in support of cotransmission ( [545]; see also [499]). Following the initial proposa1 that ATP contributed to the contractile responses of the urinary bladder to parasympathetic nerve stimulation [97], much debate followed, as indeed it did about the general concept of purinergic neurotransmission.…”
Section: Parasympathetic Cotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…This helped contribute to apparently conflicting reports by several groups characterizing purinergic stimulation as both inhibitory [83][84][85] and excitatory 28,29 under their respective recording conditions. Recent patch clamp studies undertaken by Sergeant and coworkers has provided clarifying evidence that purinergic compounds released by nerves in urethral smooth muscle tissue activate the cation-selective P2X receptors expressed on smooth muscle cell membranes and depolarize the membrane potential.…”
Section: P2x Channelsmentioning
confidence: 99%